Reductive model of the conscious mind - Galus, Wieslaw 1947-; Starzyk, Janusz 1947- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book focuses on phenomenon of consciousness in attempt to explain it on materialistic basis. It looks at consciousness from three different perspectives: a philosophical (theoretical), biological, and machine view of the brain and mind" - Provided by publisher
Keywords: Subconsciousness